The Radical Thought and Autobiography in American Literature - Houria, Mihoubi (My University, 2014)
Abstract Autobiography as a literary genre isan account of a person's life written by him. obviously an autobiography runs the danger of being highly subjective since it is confined to the author’s life, experiences, and world view. In autobiography, the author often finds an opportunity to express his own thought that can be radical.The first purpose of the article is to treat the radical thought through four American autobiographies: Frederick Douglass The Life of F. Douglass, Richard Wright’s Black Boy, Mary Grow Dog’s Lakota Women, and Henry David Thoreau’s Walden. The other objective is to shed light on how these writers tried, by narrating their lives, to convey to the reader of their radical views of society and therefore, sought to foster social reform. Frederick Douglas and Richard Wright wrote to defend and argue for abolitionism, Mary Grow Dog wrote to ask for a better place for the American Indian women in the American society, while Henry David Thoreau defended environmentalism as a philosophy of life.
Keywords: Key words: Radicalism, autobiography, abolitionism, women, Environmentalism